Robotic-Assisted Partial Nephrectomy and Adrenalectomy: Case of a Pheochromocytoma Invading into Renal Parenchyma. (20th June 2020) - Gul, Zeynep G.; Liaw, Christine W.; Reddy, Avinash; Mehrazin, Reza
Abstract : Although upper pole renal masses and adrenal masses can usually be distinguished on cross-sectional imaging, large masses can obscure the boundaries between the kidney and adrenal gland. We describe a unique case of an adrenal pheochromocytoma in a 42-year-old female who was referred for robotic partial nephrectomy. During the procedure, the patient developed severe hypertension. The case was aborted, and the workup revealed pheochromocytoma. After appropriate pretreatment, the patient underwent a successful robotic adrenalectomy and partial nephrectomy. Therefore, we recommend screening patients with hypertension and large upper pole masses for pheochromocytoma to better direct preoperative management.